2019
DOI: 10.1002/slct.201801543
|View full text |Cite
|
Sign up to set email alerts
|

TMSOTf‐Catalysed Synthesis of 2,4,5‐Trisubstituted Imidazoles from Vinyl Azides and Nitriles

Abstract: TMSOTf‐catalysed generation of 2,4,5‐trisubstituted imidazoles by a simple [3+2] addition reaction of azido chalcones and organic nitriles is described. This transformation generates two new C‐N bonds under mild reaction conditions. The substrate scope of the reaction is excellent with good number of vinyl azides and aromatic and aliphatic nitriles tolerating the reaction. It has been shown that the reaction can also be conducted under microwave condition successfully. These newly synthesized imidazoles are sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Muthusubramanian and Esmaeilpour groups have also isolated similar yields of 2,4,5trisubstituted imidazoles for reactions carried out under thermal and microwave irradiation. 43,74 It is reported that microwave-assisted organic synthesis has several advantages such as rapid homogeneous heating, suppression of side product, convenience of handling, simple work-up, short reaction time, and required less energy compared to conventional heating. 36,[41][42][43]69,[74][75][76][77] Bearing of these advantages in mind, we investigated the substrate scope under the microwave irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…Muthusubramanian and Esmaeilpour groups have also isolated similar yields of 2,4,5trisubstituted imidazoles for reactions carried out under thermal and microwave irradiation. 43,74 It is reported that microwave-assisted organic synthesis has several advantages such as rapid homogeneous heating, suppression of side product, convenience of handling, simple work-up, short reaction time, and required less energy compared to conventional heating. 36,[41][42][43]69,[74][75][76][77] Bearing of these advantages in mind, we investigated the substrate scope under the microwave irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have reported the TMSOTf-catalyzed synthesis of highly substituted imidazoles from α-azidochalcones under mild conditions [65]. As a sequel, the synthesis of oxazoles with an arylimino substituent has been accomplished in this work.…”
Section: Resultsmentioning
confidence: 99%
“…For example Harisha et al recently reported the reaction of α-azidoenones 18 with substituted nitriles to form tri-substituted NH-imidazoles 19 (Scheme 4). 23 No significant difference was observed in isolated yield for reactions run under either thermal or microwave conditions. In addition to an arylketone moiety at the C-5 position, the protocol also allowed for the incorporation of vinyl and arylhalide functional groups.…”
Section: Two-bonds Formedmentioning
confidence: 94%